Usability and performance of secure mobile messaging: M-PKI - Anuar, N.B.; Kuen, L.N.; Zakaria, O.; Gani, Abdullah; Wahab, A.W.A. (2009)
Human life style change substantially when the cellular technology goes commercial. Short Messaging Service (SMS) and Multimedia Message Service (MMS) play important roles in our daily life. The recent report carried out by Mobile Data Association (MDA) 1 shows that the yearly growth of SMS and MMS achieves 30 percent from year 2007 to 2008. Conventional SMS/MMS does not provide any protection on the text message sent. It causes the security threats such as privacy and message integrity. Mobile users seek for the solution to allow them to exchange confidential information in a safe environment. This leads to the implementation of M-PKI, which is an application that secures the mobile messaging service by using public key infrastructure (PKI). This new approach allows the end-user to send private and classified message via SMS. Besides, M-PKI offers message classification. This feature is specially designed to meet various user requirements on the level of security and performance. The usage and performance of M-PKI messaging in performing encryption and decryption process are tested on selected java-enabled phone.